The Leadership of School Principals in Shaping Teachers' Character: An Interpretive Phenomenological Study in Madrasahs in Seberang, Jambi City, Indonesia - Mustar, Mustar; Yamin, Martinis; Jamaluddin, Jamaluddin (Dinasti Publisher, 2025)
This study examines the role of school principals' leadership in shaping teachers' character in Islamic schools (madrasahs) in Jambi City, Indonesia. Using an interpretive phenomenological approach, the research explores the lived experiences of both principals and teachers in five madrasah institutions in Seberang, Jambi City. Data were collected through in-depth interviews, focus group discussions, and participant observations conducted over eight months. The findings reveal four key dimensions of principal leadership that significantly influence the shaping of teachers' character: (1) value-based leadership modeling, (2) development of institutional culture, (3) facilitation of reflective professional development, and (4) integration of spiritual-professional domains. This study contributes to the understanding of educational leadership in a religiously-oriented context, showing how school principals play a vital role as agents in developing teachers' character, which in turn impacts overall educational quality. The research addresses a significant gap in the literature by examining the influence of leadership on the formation of teachers' character in the specific cultural and religious context of Indonesian Islamic schools.